The influence of marketing strategy on business performance through absorptive capacity and customer retention in Coffee Purchases in Bekasi City - Qois Abdul Hadi; Ilham Fadhilah; Rizky Fadhilah Ardian (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2025)
This study examines the influence of marketing strategy on business performance through the mediating roles of absorptive capacity and customer retention in the coffee business sector in Bekasi City, Indonesia. The research responds to increasing competition among coffee-based micro, small, and medium enterprises (MSMEs) and the need for knowledge-based and customer-oriented strategies. A quantitative approach was employed using Structural Equation Modeling (SEM) with AMOS version 23. Data were collected from 447 respondents consisting of owners, managers, and operational staff of coffee MSMEs through structured questionnaires. The results indicate that marketing strategy has a positive and significant effect on absorptive capacity and customer retention. Absorptive capacity also positively influences customer retention and business performance, while customer retention shows a significant impact on business performance. However, the direct relationship between marketing strategy and business performance is not significant, indicating a full mediation effect. These findings emphasize that effective marketing strategies must be supported by strong organizational learning capabilities and customer retention practices to achieve sustainable business performance.